Chapter 6: Essays from the Courage and Moral Choice Project - West, Kim; Lane, Amanda; Libby, Madison (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
In this chapter, participants from the Courage and Moral Choice Project share personal essays about their experiences with the project. Teachers describe the ways in which they sought to connect the stories of moral courage with a deepened awareness of the needs and challenges in the school and wider community. One teacher described the stories as “reminders” that courage and goodness exist in the world, a world often filled with stories of despair. Another teacher, who was once described as an “at risk” student herself, also noted that the stories provide a perspective of hope. One student described how meaningful it was for her to hear stories about the many Danish citizens to shelter and transport their neighbors during the Nazi occupation. She notes, “I think more people need to be like that.”